Reading class: Disrupting power in children's literature - Botelho, Maria Jose (ScholarWorks@UMass Amherst, 2004)
The representation of Mexican American migrant farmworkers in children's literature has increased over the past 15 years, making visible a group that previously was rendered invisible in the U.S. landscape. Classifying stories about migrant agricultural laborers under the literary category of multicultural children's literature further marginalizes this population by portraying their social circumstances as private, personal, and cultural. While these stories bring the reader up close to the poverty that families endure as migrant farmworkers, they leave the socioeconomic circumstances with the families, in many ways, unlinked to power relations. In this study, I theorize a critical multicultural analysis of children's literature, which creates a space for adult and young readers alike to rethink power (i.e., inserting class into the critical dialogue on race and gender) and recognize their own social construction. Reading class, race, and gender together in children's literature about migrant farmworkers leads to reading how power is exercised in U.S. society as well as how we are implicated in its circulation: It's a waking up from the American Dream. My text collection functions as evidence of U.S. power relations of class, race, and gender—children's literature as social transcripts because a large part of U.S. ethnography is in literature (Ortner, 1991). I read these books against the history and scholarship of multicultural children's literature and the historical and sociopolitical context of migrant work in the United States. I historicize these current representations of Mexican American migrant workers within the developments of the Mexican American experience as it is rendered in children's literature. Since many of these titles fall under the genres of nonfiction and realistic fiction, I consider how these genres textually reconstruct reality by examining the discursive construction of characters and the ideological implications of how the stories close. The theoretical constructs of discourse, ideology, subjectivity, and power function as analytical tools for examining how power is exercised among the characters to locate how class, race, and gender are enacted in text, while revealing how story characters dominate, collude, resist, and take action collectively. A critical multicultural analysis of children's literature about Mexican American migrant farmworkers is a microanalysis of U.S. power relations, an examination of how power is exercised, circulated, negotiated, and transformed.